Zakonomernosti adaptatsionnoi izmenichivosti sily myshchts zhenshchin-sprinterov v protsesse stanovleniya sportivnogo masterstva - Semyonov, V. G.; Vrublevskii, E. P. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The main results of theoretical and experimental substantiation of the consistent patterns of adaptive muscles power changes and its fluxions (relative, explosive and starting power) in differently qualified women-sprinters. The authors had shown, that after special exercises repetition and active power training essentially changed interrelations between muscles power and its dynamic characteristics. The results of the research are valuable for special power training of women-sprinters.